A numerical study on the optimization of the slit shape of a jet injection propeller - Jun-Hee Lee; Ju-Han Lee; Myeong-Min Kim; Dohan Oh; Kwang-Jun Paik (International Journal of Naval Architecture and Ocean Engineering)
The shape of the slit that injects the jet from the surface of the propeller was optimized through numerical computations. The high-pressure drop on the propeller surface caused by jet injection could be improved by modifying the hydrofoil geometry of the propeller. As the cover length increased and the slit was located at the center of the propeller, the volume of jets leading to the trailing edge increased, and the propulsion performance was improved. As the height of the slit increased, the thrust increased due to the Coanda effect, and the torque decreased because of the thrust of the jet. The jet injection pattern differed according to the area of the slit and tunnel, which caused a difference in the propeller performance. The jet pattern changed according to the area of the slit and tunnel, leading to a change in propeller performance. It was effective in improving the efficiency by injecting from as wide an area as possible, and the efficiency was improved by approximately 2 % considering the pump efficiency through optimization of the slit shape.